A SNP-Based High-Density Genetic Map of Leaf and Fruit Related Quantitative Trait Loci in Wolfberry (Lycium Linn.) - Zhao, Jianhua; Xu, Yuhui; Li, Haoxia; Yin, Yue; An, Wei; Li, Yanlong; Wang, Yajun; Fan, Yunfang; Wan, Ru; Guo, Xin; Cao, Youlong (Frontiers in Plant Science, 2019)
Wolfberry (Lycium Linn. 2n = 24) fruit, Gouqizi, is a perennial shrub, traditional food and medicinal plant resource in China. Leaf and fruit related characteristics are economically important traits that are the focus for genetic improvement, but few studies into the molecular genetics of this crop have been reported to date. Here, an F1 population (302 individuals) derived from a cross between ‘NO.1 Ningqi’ (Lycium barbarum L.) and ‘Chinese gouqi’ (Lycium chinese Mill.) was constructed. We recorded fruit weight, longitude, diameter and index along with leaf length, width and index for three consecutive years from 2015 to 2017. Based on this population and these phenotypic data, we constructed the first high-density genetic map of Lycium using specific length amplified fragment sequencing (SLAF-seq) and analyzed quantitative trait loci (QTLs). The map contains 6733 single nucleotide polymorphisms and 12 linkage groups (LG) with a total map distance of 1702.45 cM and an average map distance of 0.253 cM. A total of 55 QTLs were mapped for more than two years, of which 18 stable QTLs for fruit index on LG 11, spanning an interval of 73.492–90.945 cM, were detected. qFI11-15 for fruit index was an impressive QTL with logarithm of odds (LOD) and proportion of variance explained (PEV) values reaching 11.07 and 19.7%, respectively. The QTLs on LG 11 were gathered tightly, having an average interval of less than 1 cM per QTL, suggesting that there might be a cluster region controlling fruit index. Remarkably, qLI10-2 and qLI11-2 for leaf index were detectable for three years. These results give novel insight into the genetic control of leaf and fruit related traits in Lycium and provide robust support for undertaking further positional cloning studies and implementing marker-assisted selection in seedlings.